Developing a Hypothetical Learning Trajectory for Eighth Graders’ Statistical Understanding through Techno-Ethno-Realistic Mathematics Education - Farida Nursyahidah; Wardono Wardono; Scolastika Mariani; Kristina Wijayanti (Universitas Negeri Semarang, 2026)
Statistics is an important aspect of mathematics that supports the development of students' cognitive abilities. However, understanding statistical concepts often becomes an obstacle for students. This article aims to develop and present a hypothetical learning trajectory on statistics using a techno-ethno-realistic mathematics education (TE-RME) approach. The research was conducted using a design research method that comprises three main stages: preliminary design, design experiments, and retrospective analysis. This research involved eighth-grade students at a junior high school in Semarang. The focus of this article is on the initial design stage, namely the development of a hypothetical learning trajectory that includes three main activities: (1) collecting, presenting, and interpreting data through culturally context-based video observation and spreadsheet, (2) determining the central tendency measures, and (3) determining the measure of data distribution. The series of activities in this learning trajectory is designed to help students build a deeper understanding of statistical concepts while fostering an appreciation of local culture and diversity in mathematical thinking. This hypothetical learning trajectory is designed to be implemented in experimental classes and research-based teaching using TE-RME to improve students' statistical understanding.